Plasma enhanced chemical vapor deposition growth of vanadium dioxide - LEE, Boon Peng (2019)
Vanadium Oxide interesting compound which have energy saving properties in energy conservation applications. VO2 are chosen instead of other oxidation state are partly because of their near room temperature critical phase transition temperature (Tc) and atomic structures. VO2 Exhibit reversible phase transition properties from tetragonal rutile to monoclinic structure when it exceeds 680C. To achieve high quality VO2 thin film on a soda lime glass substrate, understanding nucleation mechanism to fine tune the process condition is essential. Are discussed in this report. There are multiple deposition configurations or techniques to achieve VO2 thin film. However, Plasma Enhanced Chemical Vapor Deposition (PECVD) was used to synthesize in this project due to high deposition rate and good uniformity. The morphology of the samples was studied and analyzed using Atomic force microcopy (AFM) and scanning electron microscopy (SEM). The chemical composition and transmittance are examined using Energy dispersive X-ray spectroscopy (EDX) and UV-Vis spectroscopy (UV-Vis). Lastly the phases of VO2 thin film is recorded using X-Ray Diffraction (XRD). The experimental results show at 〖450〗^0 C growth temperature, VO2 thin film will be nucleate at optimum condition when the duration of growth duration is at 4 minutes with vacuum chamber of 1 torr, 200W of plasma generator power, argon and oxygen flow rate are at 200 and 10 standard cubic centimeters per minute respectively. The results regarding synthesis of VO2 thin film and film thermochromic properties were discussed in this report. Further studies were also recommended to optimize the effectiveness of synthesizing VO2 thin film.